Endogenously Determined Restriction of Food Intake Overcomes Excitation-Contraction Uncoupling in JP45KO Mice with Aging - Delbono, Osvaldo (2012)
The decline in muscular strength with age is disproportionate to the loss in total muscle mass that causes it. Knocking out JP45, an integral protein of the junctional face membrane of the skeletal muscle sarcoplasmic reticulum (SR), results in decreased expression of the voltage-gated Ca(2+) channel, Ca(v)1.1; excitation-contraction uncoupling (ECU); and loss of muscle force (Delbono et al., 2007). Here, we show that Ca(v)1.1 expression, charge movement, SR Ca(2+) release, in vitro contractile force, and sustained forced running remain stable in male JP45KO mice at 12 and 18 months. They also exhibit the level of ECU reported for 3–4-month mice (Delbono et al., 2007). No further decline at later ages was recorded. Preserved ECC was not related to increased expression of any protein that directly or indirectly interacts with JP45 at the triad junction. However, maintained muscle force and physical performance were associated with ablation of JP45 expression in the brain, spontaneous and significantly diminished food intake and less tendency toward obesity when exposed to a high-fat diet compared to WT. We propose that (1) endogenously generated restriction in food intake overcomes the deleterious effects of JP45 ablation on ECC and skeletal muscle force mainly through downregulation of neuropeptide-Y expression in the hypothalamic arcuate nucleus; and (2) the JP45KO mouse constitutes an invaluable model to examine the mechanisms controlling food intake as well as skeletal muscle function with aging.